Primary School STEM Education Innovation through ICT Integration for Teacher Competency Development: A Systematic Literature Review - Syahrir Syahrir; Pujiriyanto Pujiriyanto; Musdalifa As; Fahrul Arfandi M. Nur; Sakinah Fitri (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikdasmen, 2024)
This study examines the integration of Information and Communication Technology (ICT) to enhance STEM learning in primary schools. Conducted via a systematic literature review (SLR) following PRISMA guidelines, articles from 2020 to 2024 were analyzed using Scopus. The findings underscore the profound impact of ICT integration on bolstering STEM education in primary settings. Effective implementation requires tailored teacher training programs and a comprehensive understanding of primary education dynamics. Despite challenges, addressing the nuanced needs and perceptions within primary education is imperative for advancing the quality of STEM education. Consequently, providing teachers with requisite support, including targeted training initiatives and a nuanced grasp of primary education requirements, is vital for fortifying the efficacy of STEM education in the future. To conclude, fostering a synergy between STEM and ICT yields significant enhancements in primary school learning outcomes.